HUBUNGAN GAYA KEPEMIMPINAN GENERAL MANAGER DAN KOMUNIKASI INTERPERSONAL DENGAN MOTIVASI DAN KINERJA KARYAWAN PATRA JASA BALI RESORT AND VILLAS - Oktavianus Wayan Semuel (Universitas Pendidikan Nasional, 2014)
This study purpose to determine the effect of leadership style, interpersonalcommunication on motivation and performance of Patra Jasa bali Resort and Villa’semployees.The study was conducted in hospitality organizations by using employees as acorrespondent. The number of respondents in this study are 225 peoples. The data analysistechnique used path analysis (SEM Analysis) which is operated through the AMOS program,Version 20.0The results showed that leadership style and general manager interpersonalcommunication had a positive and significant impact on the motivation and performance ofemployees Patra Jasa Bali Resort and Villas.Keywords : Leadership Style, Interpersonal Communication, Motivation and EmployeePerformance Patra Jasa Bali Resort and Villas.